Exploring the Link Between Provincial Exports and Economic Growth: Evidence from Türkiye - Ахмед Юсуф Сарихан; Муса Баир (Экономика региона)
Exports play a vital role, particularly for developing countries, and economic growth remains a central goal for all nations. Over time, numerous approaches have sought to understand and explain the causal relationship between exports and macroeconomic indicators, with extensive studies conducted on the subject. This research examines the relationship between exports and economic growth using panel data analysis at the provincial level in Türkiye, offering a unique perspective compared to traditional country-level analyses. Given that international trade is often studied at the national or enterprise level, this province-focused approach provides distinctive insights. The study covers the period from 2004 to 2020 and employs the Westerlund ECM Cointegration Test, Panel ARDL, and Dumitrescu & Hurlin Causality Test as analytical methods. The findings reveal both cointegration and bidirectional causality between provincial exports and economic growth. Furthermore, increases in exports positively impact economic growth in both the short and long term. Notably, the effect is more pronounced in provinces with well-developed tourism and industrial sectors.